Forecasting inflation in Iran by applying machine learning algorithms to PPP lag - BOGER, Tal (Turkish Economic Review, 2025)
Abstract. Purchasing Power Parity (PPP) relates the prices of two countries by their exchange rates. Several economists use PPP to measure inflation in the absence of official and accu- rate government reports. In the case of Iran, the government’s official inflation figures are significantly lower than what one would expect given their economic troubles; therefore, we apply PPP to measure inflation in Iran. Because of its volatility in the short-run, PPP is often used as a long-run economic indicator. The main cause for this is that PPP is a leading indicator, creating short-term inaccuracies. However, using machine learning algorithms, we forecast both the time until there is zero PPP lag (i.e. the official and implied inflation rates are equal) and the difference between the official and implied inflation rate (allowing us to predict official inflation rates) for Iran with minimal volatility. This allows us to use PPP accurately over both the short- and long-run. Keywords: Purchasing Power Parity (PPP); Iranian inflation; Machine learning; Support vector machine; Random forest; k -nearest neighbors; Neural network JEL. D30; D63; E21.